The tax system of OECD countries and main recommendations from the Organisation: Parameters for a tax reform in Brazil - Pedro Humberto Bruno de Carvalho Junior (International Policy Centre for Inclusive Growth (IPC-IG), 2022)
This paper describes the tax systems of OECD advanced economies and assesses the entity's recommendations on tax policy, applying them to the debate around tax reform in Brazil. It is not meant as a guide for OECD taxation to be copied by Brazil, but rather to provide tools to better foster the debate around a tax reform that is economically efficient and socially inclusive. It seeks to enhance the debate around tax reform, showing current international indicators and trends and the limitations of tax reform proposals, considering international benchmarks.
Keywords: 330; tax reform; OECD; Brazil